ANALISIS SISTEM OTOMATISASI ALAT PENGUPAS TEMPURUNG KELAPA MENGGUNAKAN ARDUINO UNO - Eko Susetyo Yulianto; Doddi Yuniardi; Riyad Basir (Jurnal Teknik dan Science, 2023)
Coconut is a type of plant from the Arecaceae and the sole member of the margos. This plant lives in tropical areas such as in Indonesia. West Kalimantan, which is one of the islands that has a large area, has the potential for the utilization of this coconut. This potential is utilized as in export needs, but due to the use of traditional technology, namely using a wedge in stripping coconut husk, there is often a delay in the export process, so technology such as a coconut husk peeler with electric power is needed which aims to obtain more stripping time. fast. The research method in the design is done by reading the literature, observation, experimental and descriptive by varying the blade with an angle of 0o and 5o in order to obtain maximum results. Coconuts whose husks are peeled using a coir peeler design with variations in angles have a peeling machine capacity of 333 pieces/hour and 383 pieces/hour. This result is greater when compared to using a wedge with an average stripping time of 180 pieces/hour, so it has a percentage of 0o of 185% and 5o of 212.78% higher, so it can help increase production and help in handling the export process.